Emergence of Polycystic Neotropical Echinococcosis - Dennis Tappe; August Stich; Matthias Frosch (Emerging Infectious Diseases, 2008)
Echinococcosis is a parasitic zoonosis of increasing concern. In 1903, the first cases of human polycystic echinococcosis, a disease resembling alveolar echinococcosis, emerged in Argentina. One of the parasites responsible, Echinococcus oligarthrus, had been discovered in its adult strobilar stage before 1850. However, >100 years passed from the first description of the adult parasite to the recognition that this species is responsible for some cases of human neotropical polycystic echinococcosis and the elucidation of the parasite’s life cycle. A second South American species, E. vogeli, was described in 1972. Obtaining recognition of the 2 species and establishing their connection to human disease were complicated because the life cycle of tapeworms is complex and comprises different developmental stages in diverse host species. To date, at least 106 human cases have been reported from 12 South and Central American countries.